Code improvement, separate-effect validation, and benchmark calculation for thermal-hydraulic analysis of helical coil once-through steam generator. (15th June 2020) - Lian, Qiang; Tian, Wenxi; Gao, Xinli; Chen, Ronghua; Qiu, Suizheng; Su, G.H.
Highlights: The HCOTSG module is implemented in RELAP5. The separate-effect validation for pressure drop and heat transfer is performed. The integral calculation is performed for the HCOTSGs of IRIS and MRX. The code can be used to analyze the thermal-hydraulic behavior of HCOTSGs. Abstract: Helical coil once-through steam generators (HCOTSGs) have been widely used in the design of small modular reactor (SMR) during the past several decades. As the widely accepted system analysis code, RELAP5 underestimates the heat transfer capability and pressure drop of helical coil tube steam generators using the original geometrical parameters of HCOTSG, because the built-in thermal-hydraulic empirical correlations are only suitable for straight tubes. In this study, thermal-hydraulic models for helical coil tubes and tube bundles are implemented in RELAP5 while the original functions of the code are not affected. A new flag for helical component is proposed and heat transfer boundaries for tube side and shell side are developed. The separate-effect validations of friction factor and heat transfer in helical coil tube are carried out based on experimental data and code-to-code verification. Then, the original RELAP5 and developed RELAP5-HCOTSG are used to simulate helical coil tube steam generators of two SMRs. One is the integral reactor IRIS, and the other is MRX. The calculated results are compared to the design parameters. It shows that the HCOTSG module developed in this study can improve the capability of RELAP5 to predict the thermal-hydraulic characteristics in SMR once-through steam generators with helical coil tubes.